The anatomy of murder : ethical transgressions and anatomical science during the Third Reich - Hildebrandt, Sabine (Berghahn Books, 2016)
"This volume explores how the study of anatomy was conducted during the governance of the Third Reich, from the Third Reich's involvement with university anatomy departments to how the Third Reich implemented protocols for anatomists"--